Evaluation of Seed Yield and Yield Components of Some Chickpea Genotopes Grown under Şirnak-Idil Ecological Conditions - MATUR, İsmail and YÜCEL, Derya (MAS Journal of Applied Sciences, 2022)
This study was carried out to determine the yield and yield factors of some chickpea genotypes inŞırnak-İdil ecological conditions. In the research, 12 lines and 4 control cultivars (Arda, Azkan, Aksu andInci) totally 15 chickpea genotypes were used as material. Field experiment was carried out in Sirnak-Idilconditions, in the cultivation period (Novevember-July) of 2020/2021, in a randomized block design withthree replications. As a result of the research, although it varies according to chickpea genotypes, thenumber of days until flowering, average plant height, first pod height, the number of branches, the numberof pods, the number of grains, grain weight, grain yield, hundred grain weight, harvest index value variedbetween 115.7 and 161.7 days, between 42.9 cm and 53.5 cm, between 15.2 cm and 26.2 cm, between 2.0and 3.9, between 23.0 and 43.4, between 14.0 and 44.0, between 9.2 and 13.4 g, between 98.4 and 160.7kg da-1, between 23.3 and 37.6 g, 34.5 and 46.2%, respectively. As a result, in Sirnak/Idil ecologicalcondition, FLIP 03-104 C chickpea genotype can give better results in arid and semiarid conditions becauseof its early flowering and podding time; It was determined that Arda and FLIP 97-503 C chickpea genotypesgave better results than other genotypes examined in terms of yield and yield-related characteristics.